The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00419-007-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

An analytical solution to non-axisymmetric heat transfer with viscous dissipation for non-Newtonian fluids in laminar forced flow

Abstract: Forced convection heat transfer in a non-Newtonian fluid flow inside a pipe whose external surface is subjected to non-axisymmetric heat loads is investigated analytically. Fully developed laminar velocity distributions obtained by a power-law fluid rheology model are used, and viscous dissipation is taken into account. The effect of axial heat conduction is considered negligible. The physical properties are assumed to be constant. We consider that the smooth change in the velocity distribution inside the pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Their results highlight that the effects of the viscous dissipation parameter vary the temperature distribution. Many researchers [136][137][138][139][140][141] introduced the viscous energy dissipation on the fully developed laminar flow in circular ducts. They showed the effect of viscous dissipation on the axial distribution of wall heat flux for power-law fluids in a thermally developed region.…”
Section: Primary Effects Of Viscous Dissipationmentioning
confidence: 99%
“…Their results highlight that the effects of the viscous dissipation parameter vary the temperature distribution. Many researchers [136][137][138][139][140][141] introduced the viscous energy dissipation on the fully developed laminar flow in circular ducts. They showed the effect of viscous dissipation on the axial distribution of wall heat flux for power-law fluids in a thermally developed region.…”
Section: Primary Effects Of Viscous Dissipationmentioning
confidence: 99%
“…Most of the earlier works on forced convective heat transfer of non-Newtonian fluids, including the effects of viscous dissipation, have focused on the generalized Newtonian fluid model. The studies reported by several researchers, such as Tso et al, 2 Koliatwong et al, 3 Etemad et al, 4 Barletta, 5 and Chiba et al, 6 have included the power-law fluid model, and that of Min et al 7 has included the Bingham fluid model in delineating the consequential effects of viscous dissipation on the heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%